Advances in accounting education teaching and curriculum innovations. - Rupert, Timothy J.; Kern, Beth Burchfield, 1958- (Advances in accounting education., 2016)
Ananias Charles Littletons (1886-1974) is widely recognized as one of the founding fathers of the accounting discipline in the United States. During his lifetime, he published several books and over 100 articles in journals such as the Harvard business review, Journal of accountancy, and The accounting review. The sum of Littletons publications have contributed to the establishment of the inductive approach to accounting construction, the veracity of historical cost measurements, and the viewpoint that accounting principles and standards should guide practice. In this posthumously edited volume-the manuscript of which was discovered at the University of Illinois at Urbana-Champaign in 2014-Littleton continues these familiar themes from earlier writings but he also embarks on new lines of inquiry. The most interesting of the latter is Littletons integration of the philosophical tradition of pragmatism as a basis for his accounting theory. The content of this edited volume will be of interest to any serious student of accounting history and theory.